2013
DOI: 10.1080/0092623x.2012.736919
|View full text |Cite
|
Sign up to set email alerts
|

Marital Functioning and Psychological Distress Among Older Couples Over an 18-Month Period

Abstract: Many authors have underlined the existence of a negative association between marital functioning and psychological distress. However, little is known about the direction of this association over time among older couples. This study examined the relation over time between psychological distress and marital functioning among 394 community-dwelling couples. The authors conducted dyadic data analyses to determine whether marital functioning at baseline (T1) predicted psychological distress 18 months later (T2), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…Thus, we cannot know whether depressive symptoms predicted demand/withdraw behaviors or vice versa. Several longitudinal studies suggest a bidirectional association between depressive symptoms and relationship functioning (e.g., Davila, Karney, Hall, & Bradbury, 2003; Villeneuve et al, 2014). When we conducted follow-up analyses to examine several alternative mediation models, none of the key indirect reverse effects emerged as significant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot know whether depressive symptoms predicted demand/withdraw behaviors or vice versa. Several longitudinal studies suggest a bidirectional association between depressive symptoms and relationship functioning (e.g., Davila, Karney, Hall, & Bradbury, 2003; Villeneuve et al, 2014). When we conducted follow-up analyses to examine several alternative mediation models, none of the key indirect reverse effects emerged as significant.…”
Section: Discussionmentioning
confidence: 99%
“…Denton et al (2009) demonstrated that women diagnosed with major depressive disorder who also reported lower quality romantic relationships were less likely to recover from the depression following individual psychotherapy, medication, or a combination of both. Other studies have demonstrated varying associations between depression and marital quality depending on the length of the relationship (Maier & Priest, 2016;Villeneuve et al, 2014;Whisman, Robustelli, Beach, Snyder, & Harper, 2015). Najman et al (2013) demonstrated a reciprocal association between marital quality and depressive symptoms, with higher depression predicting lower marital quality and vice versa, in a 21-year longitudinal study of women.…”
Section: Depression and Relationship Satisfactionmentioning
confidence: 91%
“…() demonstrated that women diagnosed with major depressive disorder who also reported lower quality romantic relationships were less likely to recover from the depression following individual psychotherapy, medication, or a combination of both. Other studies have demonstrated varying associations between depression and marital quality depending on the length of the relationship (Maier & Priest, ; Villeneuve et al., ; Whisman, Robustelli, Beach, Snyder, & Harper, ). Najman et al.…”
Section: Depression and Relationship Satisfactionmentioning
confidence: 96%
“…demonstrated both cross-sectionally and longitudinally (e.g., Davila, Karney, Hall, & Bradbury, 2003;Villeneuve et al, 2014;Whisman, Uebelacker, & Weinstock, 2004).…”
mentioning
confidence: 99%